Thalidomide Mitigates Apoptosis via Endoplasmic Reticulum Stress in Diabetic Nephropathy - Zhang, Hong-Xia; Yuan, Jie; Li, Rong-Shan (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2022)
Background: Previous studies have shown that endoplasmic reticulum (ER) stress is related to the apoptosis in the development of diabetic nephropathy (DN) and thalidomide (Thd) has renalprotective effects by suppressing inflammation and proliferation of MCs in DN. However, the effect of Thd on the apoptosis of MCs in DN remains largely unclear. The present research is designed to explore the effect of Thd on apoptosis in DN and the related mechanisms. Objective: The study is designed to examine the effect and mechanism of Thd on apoptosis in type 2 diabetic mice and high glucose (HG)-induced MCs. Methods: We first evaluated the ER stress markers and apoptosis-related proteins with the treatment of Thd in type 2 diabetic mice and MCs in vitro under HG conditions. MTT assay was used to assess cell viability. Additionally, we evaluated the effect of Thd treatment upon MC apoptosis through flow cytometry. Real-time polymerase chain reaction (RT-PCR) and Western blot were performed to evaluate genes and protein expression related to ER stress and apoptosis. Results: The levels of blood urea BUN, CREA, Urine albumin, and UACR in diabetic mice were observed to be significantly reduced after 8 weeks of intervention with Thd. And also, there were upregulated glucose-regulated protein 78 (GRP78), Caspase-12, and downregulated B-cell lymphoma 2 (Bcl-2) in glomeruli of DN mice. In vitro, compared with the HG group, MC apoptosis reduced dramatically with Thd treatment along with upregulation of Bcl-2 and downregulation of Bax. At the same time, ER stress markers GRP78, C/EBP homologous protein (CHOP), and Caspase-12 were also mitigated following the Thd treatment. Conclusion: The present study indicates that Thd might reduce the ER stress in DN via downregulating GRP78, CHOP, and Caspase12 expressions, ultimately mitigating MCs apoptosis.
Keywords: thalidomide